Hierarchically ordered meso/macroporous γ-alumina for enhanced hydrodesulfurization performance - Han, D.; Li, X.; Zhang, Lei; Wang, Y.; Yan, Z.; Liu, Shaomin (Elsevier BV, 2012)
The facile synthesis of three-dimensionally ordered macroporous (3DOM) γ-alumina with high thermal stability and the performance test in hydrodesulfurization (HDS) of dibenzothiophene (DBT) were investigated. The synthesis strategy in this work is based on a sol–gel process using a colloidal crystal template method in which a triblock copolymer F127 is employed as the mesoporous structure-directing agent. The as-prepared samples were characterized by means of techniques such as thermogravimetric analysis, XRD measurement, nitrogen adsorption and desorption, SEM and TEM investigations. These results showed that all the synthesized alumina samples possess a highly ordered macroporous structure. The sample calcined at 800 °C with a surface area of 79 m2 g−1 exhibited the ordered mesopores within the walls of the macroporous cages. The co-existence of the interconnected macroporous and mesoporous structure of the prepared γ-alumina enables it to be an effective catalyst support with favorable accessibility of the reactants to the active sites. HDS of DBT was chosen to test the catalytic performance of the 3DOM γ-alumina supported CoMo-based catalyst which displayed a higher desulfurization ratio of 98.23% in striking contrast to 70.60% with commercial mesoporous alumina support under the reaction temperature of 300 °C.